Drag Reduction Using Lubricant‐Impregnated Anisotropic Slippery Surfaces Inspired by Bionic Fish Scale Surfaces Containing Micro‐/Nanostructured Arrays - Rong, Wanting; Zhang, Haifeng; Zhang, Tengjiao; Mao, Zhigang; Liu, Xiaowei; Song, Keguan (Advanced engineering materials, 2021)
Inspired by the bionic fish scale surfaces containing micro/nanostructured arrays, herein, the applications of lubricant‐impregnated anisotropic slippery surfaces (LIASSs) using laser ablation of aluminum–magnesium alloys are proposed. Different hydrophobic properties are presented on the LIASSs along the parallel direction and the reverse direction defined as directions A and B of bionic fish scale micro/nanostructures. A self‐assembled solid–liquid interface friction test device is set up to demonstrate the drag reduction property of LIASSs. The drag reduction ratios are found to be 51.09% and 44.88% along directions A and B, respectively. With the increase in the velocity, the drag reduction ratios of LIASSs can also be kept near 50%. Simulation models are established to study the drag reduction mechanism of LIASSs in laminar flows. Liquid–liquid repellency has a lubricating effect that can increase mobility and reduce viscous resistance. In this way, it improves the fluidity of the liquid and reduces drag. The drag reduction ratio in direction A is superior to that in direction B for the same flow velocity. The results of the simulation are consistent with the experiments results. LIASSs represents an effective strategy to drag reduction and reducing energy consumption in liquid directional transport and marine vessels. Lubricant‐impregnated anisotropic slippery surfaces (LIASSs), which are bionic surfaces containing micro‐/nanostructured arrays impregnated with lubricating oils. Different hydrophobic and drag reduction properties are presented on the LIASSs along the parallel direction and the reverse direction of bionic fish scale micro‐/nanostructures. LIASSs represent an effective strategy to drag reduction and reducing energy consumption in liquid directional transport and marine vessels.